Encapsulated tri-band terahertz (THz) swiveled dielectric resonator antenna (DRA) with substrate integrated waveguide (SIW) and photonic band gap (PBG) crystal for gain enhancement - G. Divya; KJagadeesh Babu; I. Balakrishna; Tathababu Addepalli; Dunya Zeki Mohammed; Z. Zakaria; Ahmed J. A. Al-Gburi (Scientific Reports)
Abstract This article investigates the innovative integration of a substrate-integrated waveguide (SIW) with a nested photonic bandgap (PBG) crystal to enhance the performance of a swiveled dielectric resonator antenna (DRA). The study focuses on designing the SIW, the PBG crystal, and the novel shape of the DRA, which is swiveled and embedded within the SIW and photonic crystal structure. The aperture-fed DRA is analyzed over the 0.1–10 THz frequency range. The proposed encapsulated SIW-PBG antenna demonstrates resonances at 2.5 THz, 3.5 THz, and 5.2 THz. Utilizing a periodically grooved silicon substrate surrounding the SIW significantly enhances the gain, achieving values of 6.75 dBi, 6.86 dBi, and 6.82 dBi, respectively. Rigorous parametric analysis is conducted to optimize the design and validate the results.